2011
DOI: 10.1080/09602011.2011.630882
|View full text |Cite
|
Sign up to set email alerts
|

Prospective memory rehabilitation based on visual imagery techniques

Abstract: Despite the frequency of prospective memory (PM) problems in the traumatic brain injury (TBI) population, there are only a few rehabilitation programmes that have been specifically designed to address this issue, other than those using external compensatory strategies. In the present study, a PM rehabilitation programme based on visual imagery techniques expected to strengthen the cue-action association was developed. Ten moderate to severe chronic TBI patients learned to create a mental image representing the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 39 publications
2
37
0
Order By: Relevance
“…However, visualization was beneficial for naturalistic PM performance specifically among seropositive individuals with low time-based PM and/or intact learning. The benefit of visualization on event-based PM observed among this subset of young HIV+ individuals is consistent with prior studies in healthy young adults (Paraskevaides et al, 2010; McFarland & Glisky, 2012), older adults (Altgassen et al, 2015), and clinical samples (Grilli & McFarland, 2011; Potvin et al, 2011). Additionally, these data provide further evidence that inclusion of implementation intentions is not required for visualization to bolster event-based PM (Meeks & Marsh, 2010; McFarland & Glisky, 2012).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…However, visualization was beneficial for naturalistic PM performance specifically among seropositive individuals with low time-based PM and/or intact learning. The benefit of visualization on event-based PM observed among this subset of young HIV+ individuals is consistent with prior studies in healthy young adults (Paraskevaides et al, 2010; McFarland & Glisky, 2012), older adults (Altgassen et al, 2015), and clinical samples (Grilli & McFarland, 2011; Potvin et al, 2011). Additionally, these data provide further evidence that inclusion of implementation intentions is not required for visualization to bolster event-based PM (Meeks & Marsh, 2010; McFarland & Glisky, 2012).…”
Section: Discussionsupporting
confidence: 87%
“…This hypothesis was supported by Brewer and Marsh (2010), who demonstrated that deeper encoding of the cue-to-context link by way of visualization was associated with better accuracy on event-based PM tasks. Further support for the association between brief visualization exercises utilized during the encoding stage of laboratory PM tasks and enhanced event-based PM has been shown in healthy young adults (Paraskevaides et al, 2010; McFarland & Glisky, 2012; Altgassen et al, 2015), older adults (Altgassen et al, 2015) individuals with traumatic brain injury (Potvin et al, 2011), and a mixed clinical sample with memory impairments (Grilli & McFarland, 2011). Visualization has also been associated with improvements in time-based PM in young adults (Altgassen et al, 2015), older adults (Altgassen et al, 2015), adult social drinkers (Griffiths et al, 2012), and individuals with moderate-to-severe traumatic brain injury (Potvin et al, 2011).…”
Section: Introductionmentioning
confidence: 90%
“…Time since injury ranged from 1.01 to 14.4 years ( mean = 5.3 years, SD = 3.78). Strategy-based interventions were used in four studies (O’Neil-Pirozzi et al, 2010; Vas et al, 2011; Dawson et al, 2013; Twamley et al, 2014), drill and practice training (including computer-assisted training) in six (Ryan and Ruff, 1988; Baribeau et al, 1989; Ruff et al, 1989; Rattok et al, 1992; Potvin et al, 2011; Nelson et al, 2013), and a combination of both in four studies (Goranson et al, 2003; Tiersky et al, 2005; Wai-Kwong Man et al, 2006; Cantor et al, 2014). An active control group was used in seven studies ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…The average PEDro score was 5.64/9 ( SD = 0.84). Seven studies were RCTs (Ryan and Ruff, 1988; Ruff et al, 1989; Tiersky et al, 2005; Vas et al, 2011; Nelson et al, 2013; Twamley et al, 2014) and seven were non-randomized controlled studies (Baribeau et al, 1989; Rattok et al, 1992; Goranson et al, 2003; Wai-Kwong Man et al, 2006; O’Neil-Pirozzi et al, 2010; Potvin et al, 2011; Dawson et al, 2013; Cantor et al, 2014). Four of the studies confirmed assessor blinding, whilst three reported intention-to-treat.…”
Section: Resultsmentioning
confidence: 99%
“…20 In general, such techniques focus on directing attention to and elaborating in some meaningful way upon the information to be remembered, with the aim of facilitating subsequent retrieval. 29 Self-awareness techniques that have focused upon improving the patient's knowledge of the manifestations of memory impairments, combined with compensatory prospective cueing techniques, have also been associated with improved performance on prospective • Clearly define intervention goals; For example, instruction in the PQRST (Preview, Question, Read, Self-Recitation, Test) method has been associated with improvement in performance on standardized verbal memory measures.…”
Section: Recommendations and Literature Reviewmentioning
confidence: 99%